Ecological competition and the incidence of Acinetobacter baumannii bloodstream infections in a teaching hospital in Southeastern Brazil - Lastoria, Letícia Chamma; Caldeira, Sílvia Maria [UNESP]; Moreira, Rayana Gonçalves; Akazawa, Renata Tamie; Maion, Júlia Coutinho; Fortaleza, Carlos Magno Castelo Branco [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2014)
Introduction Recently, pathogen ecology has been recognized as an important epidemiological determinant of healthcare-associated infections (HAIs). Acinetobacter baumannii is one of the most important agents known to cause HAIs. It is widespread in healthcare settings and exhibits seasonal variations in incidence. Little is known about the impact of competition with other hospital pathogens on the incidence of A. baumannii infection. Methods We conducted an ecological study, enrolling patients who presented with healthcare-associated bloodstream infections (HA-BSIs) from 2005 to 2010 at a 450-bed teaching hospital in Brazil. HA-BSIs were said to be present when bacteria or fungi were recovered from blood cultures collected at least three days after admission. Monthly incidence rates were calculated for all HA-BSIs (overall or caused by specific pathogens or groups of pathogens). Multivariate Poisson regression models were used to identify the impacts of the incidence of several pathogens on the incidence of A. baumannii. Results The overall incidence rate of HA-BSI caused by A. baumannii was 2.5 per 10,000 patient-days. In the multivariate analysis, the incidence of HA-BSI caused by A. baumannii was negatively associated with the incidence rates of HA-BSI due to Staphylococcus aureus (rate ratio [RR]=0.88; 95% confidence interval [CI]=0.80-0.97), Enterobacter spp. (RR=0.84; 95%CI=0.74-0.94) and a pool of less common gram-negative pathogens. Conclusions Our results suggest that competition between pathogens influences the etiology of HA-BSIs. It would be beneficial to take these findings into account in infection control policies.
Keywords: Acinetobacter baumannii; Bloodstream infections; Ecological competition